ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF EXPENDITURES BUDGET AT THE OFFICE OF THE REGIONAL INSPECTORATE, MAMUJU REGENCY, 2019-2021 - Wulan Ayuandiani (SEAN Institute, 2022)
This study aims to analyze the level of effectiveness and efficiency in managing the expenditure budget, through data on direct expenditure targets, expenditure budget targets, direct expenditure realization and expenditure budget realization at the Regional Inspectorate Office of Mamuju Regency, 2019-2021. Data analysis methodused in this study is descriptive quantitative analysis, namely a data analysis tool that functions to describe conditions related to technical budget management from the results of interviews and descriptionsresults of calculating the ratio of effectiveness and efficiency of budget management at the Regional Inspectorate Office of Mamuju Regency. The results of this study show: First, the effectiveness of the spending budget during 2019-2021 has an average value of 97.85% which indicates an effective condition. Second, the condition for budget efficiency during 2019-2021 has an average value of 35.86% which indicates a very efficient condition. The condition of effectiveness and high efficiency in budget management at the Regional Inspectorate of Mamuju Regency can be an example for regional apparatus agencies in the West Sulawesi region.